SOIL IMPROVEMENT BY SAND DRAIN /REVIEW - Safa Alaa Hussein; Mohammed Abdlamer Abdlhusen (Journals Park Publishing, 2025)
Soil techniques used in stabilizing weak soils such as clay or saline soils are very diverse in terms of the mechanisms used and the material used, in addition to the multiple methods in their implementation. Over time, the construction industry has embraced a number of effective soil improvement techniques for liquefaction mitigation. In this research paper, a review was made on soil stabilization techniques and was reinforced by some research that adopted some of these techniques. The focus was on one of the vertical methods, which is called sand drains, and this method was explained in detail with some research that adopted this method to stabilize the soil. Also in this research, some of the soil's mechanical characteristics represented by (tensile strength), (shear strength) and (Compressibility) of soil, were explained, in addition to mentioning a group of researches that were explained and adopted.
Keywords: Sand Drain, Vertical drains, Compressibility of soil, Soil improvement, shear strength of soil, tensile strength of soil.